A study of the sources and chronology of events pertaining to Philippine library history from the sixteenth to the end of the nineteenth century - Hernandez, Vicente S. (1994)
Though libraries have existed for centuries, library science is still a young profession developing its body of knowledge. In the present research, 217 sources and facts on Philippine library history from the sixteenth century to the end of the nineteenth have been compiled and abstracted. The search for source materials in the libraries, museums, and archives of Metro Manila have been limited to this historical period. The historical narrative that follows is divided chronologically into centuries.